Broad genomic workup including optical genome mapping uncovers a DDX3X: MLLT10 gene fusion in acute myeloid leukemia - Nilius-Eliliwi, Verena; Tembrink, Marco; Gerding, Wanda Maria; Lubieniecki, Krzystof P.; Lubieniecka, Joanna M.; Kankel, Stefanie; Liehr, Thomas; Mika, Thomas; Dimopoulos, Fotios; Döhner, Konstanze; Schroers, Roland; Nguyen, Hoa Huu Phuc; et al. (Frontiers in Oncology, 2022)
In acute myeloid leukemia (AML), treatment decisions are currently made according to the risk classification of the European LeukemiaNet (ELN), which is based on genetic alterations. Recently, optical genome mapping (OGM) as a novel method proved to yield a genomewide and detailed cytogenetic characterization at time of diagnosis. A young female patient suffered from a rather unexpected aggressive disease course under FLT3 targeted therapy in combination with induction chemotherapy. By applying a “next-generation work up” strategy with OGM and whole exome sequencing (WES), a DDX3X::MLLT10 gene fusion could be detected, otherwise missed by routine diagnostics. The involvement of the DDX3X::MLLT10 gene fusion in a female is intriguing, as the DDX3X gene, located on the X chromosome is known to escape random X-inactivation in females and so far has not been reported in female AML patients. Furthermore, several aspects of lineage ambiguity not shown by standard diagnostics were unraveled such as deletions of SUZ12 and ARPP21, as well as T-cell receptor recombination. In summary, the detection of this particular gene fusion DDX3X::MLLT10 in a female AML patient, as well as the findings of lineage ambiguity are potential explanations for the aggressive course of disease. Our study demonstrates that OGM can yield novel clinically significant results, including additional information helpful in disease monitoring and disease biology.